Be a better reader - Smith, Nila Banton (Pearson, 2009)
BABR consists of eight levels that correspond to reading levels 3-10. Each level introduces key reading, comprehension, and study skills, and provides practice to apply these skills. Since all texts share a similar design and format, they can be used in a variety of classroom settings with students working below, at, or above a specific reading level.